Five year trends (2008–2012) in cardiac implantable electrical device utilization in five European nations: a case study in cross-country comparisons using administrative databases. Issue 4 (14th June 2017) - Banks, Helen; Torbica, Aleksandra; Valzania, Cinzia; Varabyova, Yauheniya; Prevolnik Rupel, Valentina; Taylor, Rod S; Hunger, Theresa; Walker, Simon; Boriani, Giuseppe; Fattore, Giovanni; ,
Abstract: Aims: Common methodologies for analysis of analogous data sets are needed for international comparisons of treatment and outcomes. This study tests using administrative hospital discharge (HD) databases in five European countries to investigate variation/trends in pacemaker (PM) and implantable cardioverter defibrillator (ICD) implant rates in terms of patient characteristics/management, device subtype, and initial implantation vs. replacement, and compares findings with existing literature and European Heart Rhythm Association (EHRA) reports. Methods and results: HD databases from 2008 to 2012 in Austria, England, Germany, Italy and Slovenia were interrogated to extract admissions (without patient identification) associated with PM and ICD implants and replacements, using direct cross-referencing of procedure codes and common methodology to compare aggregate data. 1 338 199 records revealed 212 952 PM and 62 567 ICD procedures/year on average for a 204.4 million combined population, a crude implant rate of about 104/100 000 inhabitants for PMs and 30.6 for ICDs. The first implant/replacement rate ratios were 81/24 (PMs) and 25/7 (ICDs). Rates have increased, with cardiac resynchronization therapy (CRT) subtypes for both devices rising dramatically. Significant between- and within-country variation persists in lengths of stay and rates (Germany highest, Slovenia lowest). Adjusting for age lessened differences for PM rates, scarcely affected ICDs. Male/female ratios remained stable at 56/44% (PMs) and 79/21% (ICDs). About 90% of patients were discharged to home; 85–100% were inpatient admissions. Conclusion: To aid in policymaking and track outcomes, HD administrative data provides a reliable, relatively cheap, methodology for tracking implant rates for PMs and ICDs across countries, as comparisons to EHRA data and the literature indicated.